Comparative Study of High Calcium and High Iron Filter Media of Unaerated and Aerated Steel Slag Filter Systems in Removing Phosphorus - R, Hamdan; Zu Nurain Ahmad, Siti; Nazirah Mohd Arshad, Nur’ain (International Journal of Engineering and Technology, 2018)
Improper wastewater treatment will accelerate eutrophication in waterbody due to phosphorus content in wastewater. However, to remove wastewater from requires a high and complex processes. This study was conducted to explore an alternative treatment of phosphorus removal using steel slag filter system in particular of affinity different chemical composition of steel slag. Therefore, this study has been designed for comparisons between steel slag of high composition of iron (Filter HFe) and steel slag of high composition of calcium (Filter HCa) when used as the filter media of unaerated (UEF) and aerated (AEF) lab-scale column filters in removing phosphorus. Both Filter HFe and Filter HCa were continuously running for three months using 25 mg/L synthetic phosphorus wastewater of different pH systems (pH 3, pH 5, pH 7, pH 9, pH 11 and control using distilled water) as the influents. Sampling was done weekly for analysis of pH values, phosphorus (in the form of orthophosphate) removal efficiency, and concentration of Ca, Mg and Fe in the effluents. The results showed that Filter HFe has excellent (>59%) orthophosphate removal efficiency at acidic systems (pH 3 and pH 5 systems) and average removal efficiency (21-87%) at pH 7, pH 9, pH 11 systems. Also, unaerated systems performed better compared to aerated systems. Meanwhile, for Filter HCa, orthophosphate removal efficiencies for all pH systems were better (80-100%) compared to Filter HFe.Â